METHOD FOR INITIATION OF WELL CHARGES OF EXPLOSIVE MATERIALS - Voroteliak Harold Andriiovych; Monakov Valentyn Fedorovych; Shevchenko Serhii Vasyliovych; Haponenko Anatolii Leonidovych; Krysin Roderik Symonovych (2006)
The invention relates to blasting operations in mining and is intended for explosion breaking of rocks at development of minerals or at construction of objects for different purposes. This method includes formation of air cavity in well by the unit for cavity formation, with installation over the air cavity of cumulative appliance, intermediate detonator with detonating fuse over cumulative appliance, with filling explosive substance and formation of filling and with supply of explosion pulse through detonating fuse. At that the intermediate detonator is installed over the cumulative unit at distance not less than 2 diameters of the air cavity and after that the well is filled with explosive substance, this covers the intermediate detonator by layer not smaller than height of the cumulative unit. The air cavity is formed by unit for formation of cavity at axis or at side of the well. Due to enhancement of initiating pulse and stabilization of detonation effectiveness of the explosive destruction of rocks is increased, with decrease of specific consumption of explosive substance, with increase of possibilities of the method at its implementation in watered wells. Изобретение относится к подрывным работам в горной промышленности и предназначено для взрывчатой отбивки горных пород при разработке полезных ископаемых или сооружении объектов разного назначения. Способ включает создание в буровой скважине воздушной полости устройством формирования полости, установку над воздушной полостью кумулятивного устройства, промежуточного детонатора с детонирующим шнуром над кумулятивным устройством, заполнение взрывчатого вещества, формирование забивки и подачу взрывного импульса по детонирующему шнуру. При этом промежуточный детонатор устанавливают над кумулятивным устройством на расстоянии не меньше 2 диаметров воздушной полости и далее заполняют скважину взрывчатым веществом, которое покрывает промежуточный детонатор слоем не меньше высоты кумулятивного устройства. Воздушную полость создают устройством формирования полости по оси или стороне буровой скважины. Благодаря усилению инициирующего импульса и стабилизации детонации повышается эффективность взрывного разрушения горных пород, уменьшается удельный расход взрывчатого вещества, расширяются возможности способа при использовании его в обводненных скважинах. Винахід належить до підривних робіт у гірничій промисловості і призначений для вибухового відбою гірських порід при розробці корисних копалин чи спорудженні об'єктів різного призначення. Спосіб включає створення у свердловині повітряної порожнини пристроєм формування порожнини, установку над повітряною порожниною кумулятивного пристрою, проміжного детонатора з детонуючим шнуром над кумулятивним пристроєм, заповнення вибухової речовини, формування забивки та подачу вибухового імпульсу по детонуючому шнуру. При цьому проміжний детонатор установлюють над кумулятивним пристроєм на відстані не менше 2 діаметрів повітряної порожнини і потім заповнюють свердловину вибуховою речовиною, яка покриває проміжний детонатор шаром не меншим від висоти кумулятивного пристрою. Повітряну порожнину створюють пристроєм формування порожнини по осі або боку свердловини. Завдяки посиленню ініціюючого імпульсу і стабілізації детонації підвищується ефективність вибухового руйнування гірських порід, зменшується питома витрата вибухової речовини, розширюються можливості способу при використанні його в обводнених свердловинах.